Analisis Kelayakan Nilai Tahanan Pentanahan Jaringan Distribusi di PT. PLN (PERSERO) ULP Bumiayu - Isnu Gita Kumara; Rizki Noor Prasetyono (Journal of Electronic and Electrical Power Applications, 2021)
The grounding system is direct protection against instrumentality and human. The grounding process is carried out using the principle of creating a path for the fault current to the ground and making the equipment have a potential that is close to the value of the ground potential. The supply of a grounding system should be supported by the grounding resistance worth needed by PUIL, which is below 5 Ohm. To maintain the value of grounding resistance, it is necessary to check each 6 months in step with the standards of PUIL. The grounding test was carried out using an earth tester. In the analysis of the 7 grounding points of the PT. PLN (Persero) ULP Bumiayu concluded that there are 4 grounding points that have met PUIL standards because the value of their grounding resistance is below 5 Ohm. Meanwhile, the other 3 points haven't met PUIL standards because they are worth more than 5 Ohm